TANTANGAN PENERAPAN SYARIAT ISLAM DALAM SEKTOR PERBANKAN DI ACEH - Munawar Rizki Jailani; Danial; Angga Syahputra (JESKaPe: Jurnal Ekonomi Syariah, Akuntansi dan Perbankan, 2021)
The application of Islamic Sharia in the banking sector in Aceh is an attempt to realize an Islamic legal system in the banking sector in Aceh. This study examines the challenges faced during the process of implementing Islamic law in the banking sector in Aceh. This research is qualitative research with a descriptive approach. The data used in this study consisted of interviews with those involved in the process of implementing Islamic Sharia in the banking sector and other references. The results of the study show that there are several factors that become challenges and obstacles in the implementation of Islamic Sharia in the banking sector in Aceh, namely; lack of human resources, limited local government authority, lack of government attention, and external factors.